DERAJAT APOPTOSIS SEL GANGLION RETINA PASCA PEMBERIAN TAMBAHAN EKSTRAK MORINGA OLEIFERA ORAL DIBANDINGKAN DENGAN TERAPI STANDAR Studi Eksperimental pada Tikus Wistar Model Methanol Toxic Optic Neuropathy: Oral Presentation - Experimental Study - Resident - ADELIA BAYU ISFANDIARI; RISKI PRIHATNUNGTIAS; FIFIN LUTHFIA RAHMI (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Methanol toxic optic neuropathy can lead to retinal ganglion cell apoptosis which causes visual disturbance. Moringa oleifera has been reported to have an anti-inflamatorry effect that can prevent inflammatory mediators from being relased in methanol toxic optic neuropathy Methods : Twenty-one Wistar methanol toxic optic neuropathy were divided into 3 groups, namely base line group, control group that given intravenous methylprednisolone 4.5mg/6 hours for 3 days, and given standard theraphy and additional administration of oral Moringa oleifera 300mg/kgbodyweight/day for 4 weeks. Assessment of the degree of apoptosis by Anatomical Pathology with histopatolocigal scaoring. The study used Mann Whitney comparative hypothesis test (Significant p<0.05) Results : The degree of retinal ganglion cell apoptosis was significantly lower in the treatment and standard therapy groups compared to the base line group. The treatment group compared to the standard therapy group was not significantly different (p = 1,000) Conclusion : The degree of retinal ganglion cell apoptosis in rat model methanol toxic optic neuropathy was not significantly different between the group that was given additional oral Moringa oleifera extract compared to the standard theraphy group